Characterization of the drag-reducing nature of long-chain polymer–water solutions through atomization. Issue 5 (4th July 2018) - Devrani, Shitanshu; Tiwari, Rahul Kumar; Sharma, Rajat; Rajesh, Mathur P.; Kapoor, Ashish
Abstract: Inclusion of minute concentrations of elongated long chain polymers is known to exhibit drastic reduction in frictional losses for turbulent fluid flows. The polymer chains interact with solvent molecules to act as eddy stress absorbers causing reduction in drag and inducing the viscoelastic nature in the fluid layer. In this work, we propose a characterization method for viscoelastic behavior of polymer-water solutions using a spray atomization experiment. The methodology is demonstrated for polyacrylamide and polyethylene oxide-based aqueous solutions. The experimental technique assesses the nature of the fluid using a predefined parameter, impact ratio (R). Computational fluid dynamics simulations of spray atomization are performed to validate the experimental values of the impact ratio. The simulation results indicate coherence with the experimental data, and are concordant with the reported behavior of such solutions in the literature.